Enhancement of fracture toughness of hierarchical carbon fiber composites via improved adhesion between carbon nanotubes and carbon fibers. (April 2015) - Kim, Hansang; Oh, Eugene; Hahn, H. Thomas; Lee, Kun-Hong
Abstract: Hierarchical +1 composites consisting of carbon fibers with carbon nanotubes (CNTs) grown onto them and an epoxy matrix were processed, and the mode I fracture toughness of these composites was evaluated. The mode I fracture toughness of the initial batches of the hierarchical composites was lower than that of the baseline samples without CNTs. Hence, efforts to enhance the adhesion between carbon fibers and CNTs were made, resulting in enhanced adhesion. The enhanced adhesion was confirmed by Scotch tape tests and mode I fracture toughness tests followed by fractographic studies. The mode I fracture toughness of the hierarchical composites with enhanced adhesion was 51% and 89% higher than those of the baseline samples and hierarchical composites with poor adhesion, respectively. Moreover, fractographic studies of the fracture surfaces of the hierarchical composites with enhanced adhesion showed that CNTs were still attached to carbon fibers even after the mechanical tests.